A leucoplasia pilosa oral como um possível marcador de comprometimento imune : estudo citopatológico em pacientes submetidos à terapia imunossupressora - Coelho, Diego da Cruz (2014)
The oral hairy leukoplakia (OHL) is a non-malignant epithelial lesions that usually occurs along the side edges of the tongue caused by the Epstein -Barr virus (EBV). This disease is almost exclusively seen in immunocompromised patients, particularly in individuals infected with human immunodeficiency virus (HIV). However, the OHL is related to immunosuppression in general, been described in patients receiving immunosuppressive therapy. The diagnosis of OHL in its clinical or subclinical form, can be done through the detection of EBV cytopathic effects in epithelial cells. Thus, the proposition of this study was to evaluate the oral hairy leukoplakia as a possible marker of immune impairment, through a cytological study in patients undergoing immunosuppressive therapy. 40 patients with autoimmune diseases were evaluated under immunosuppressive treatment, recruited from spontaneous demand of a population of patients regularly treated at the Department of Rheumatology, University Hospital, Federal University of Sergipe. Intraoral history and physical examination were performed, and soon after, two sweeps lateral border of the tongue, one for each side, then the construct two smears on conventional glass slides to be stained by the Papanicolaou technique were performed. Subsequently consulted medical records in order to collect data regarding the diagnosis of the underlying disease, time since diagnosis, type and duration of immunosuppressive therapy and WBC count. Stained by Papanicolaou smears were evaluated for representative nuclear changes cytopathic effect of EBV, which represent the criterion of cytological diagnosis of oral hairy leukoplakia. Most of the examined patients were females (70%) and the overall mean age was 40.5±16.1 years. Subclinical LPO was observed in 52.5% of patients. Thus, the use of shaved bilateral language for cytological diagnosis of subclinical LPO as clinical and laboratory monitoring tool immunosuppressed patients, in order, ultimately, minimize the occurrence of opportunistic diseases through modulation of therapy used is suggested.